2015
DOI: 10.1039/c5ra09327a
|View full text |Cite
|
Sign up to set email alerts
|

Understanding integrated effects of humidity and interfacial transfer film formation on tribological behaviors of sintered polycrystalline diamond

Abstract: Polycrystalline diamond (PCD) used in down-hole tool applications is ideally suit for harsh environments such as drilling at circulation break and poor lubrication, in which the water molecules of physical and chemical adsorption can severely affect the tribochemistry effect across cutting interface. Here, tribological behaviors of PCD are studied in a controlled humid atmosphere (5%-50% RH). The friction coefficient is ~ 0.04 under 5% RH condition, which is significantly increased to ~ 0.11 under 50% conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 53 publications
2
19
0
Order By: Relevance
“…The 100 V ta-C coating presents a much higher wear rate with a longer running-in cycles despite of having higher hardness of ta-C coating. This severe wear with longer runningin cycles agrees well with previous reports [5,18,19]. During the running-in cycles, the abrasive particles generated from the surface of 100 V ta-C coating with higher hardness results in severe wear with disturbing to form a transfer layer on the wear scar.…”
Section: Effect Of Substrate Bias On Wear Behaviorsupporting
confidence: 91%
“…The 100 V ta-C coating presents a much higher wear rate with a longer running-in cycles despite of having higher hardness of ta-C coating. This severe wear with longer runningin cycles agrees well with previous reports [5,18,19]. During the running-in cycles, the abrasive particles generated from the surface of 100 V ta-C coating with higher hardness results in severe wear with disturbing to form a transfer layer on the wear scar.…”
Section: Effect Of Substrate Bias On Wear Behaviorsupporting
confidence: 91%
“…9(b)) and Al 2 O 3 ( Fig. 9(d)) presents characteristic peaks proving the existence of SiC [26], Si 3 N 4 [27] and Al 2 O 3 [25]. These confirm that no other materials are observed on the wear scars of SiC, Si 3 N 4 and Al 2 O 3 balls.…”
Section: Raman Spectrum Analysissupporting
confidence: 71%
“…However, the specific friction and wear mechanism of ceramics sliding with PDC under humidity conditions is complex. In previous studies, under 5%‐50% RH, we have found that the formation of transfer films at the sliding interfaces significantly affected the tribological behavior of Si 3 N 4 and PDC . Nevertheless, when RH level reached and exceeded 55%, a totally different wear mechanism of Si 3 N 4 arose.…”
Section: Introductionmentioning
confidence: 88%
“…In previous studies, under 5%-50% RH, we have found that the formation of transfer films at the sliding interfaces significantly affected the tribological behavior of Si 3 N 4 and PDC. 14 Nevertheless, when RH level reached and exceeded 55%, a totally different wear mechanism of Si 3 N 4 arose. Consequently, the effects of RH levels on the wear mechanism should be systematically investigated via exploring interfacial tribochemical reactions.…”
Section: Introductionmentioning
confidence: 99%